2010
DOI: 10.1007/s00216-009-3341-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of microwave-assisted enzymatic digestion and tandem mass spectrometry for the identification of protein residues from an inorganic solid matrix: implications in archaeological research

Abstract: A method based on microwave-assisted enzymatic digestion and liquid chromatography-tandem mass spectrometry analysis is presented for the identification of proteins incorporated within solid matrices using protein standards bound to experimental cooking pottery as a validation model. The implementation of microwave irradiation allowed for a significant decrease in overall analysis time in addition to select enhancement of peptide recovery as determined by label-free relative quantitation. We envision that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…In one of the most surprising recent examples, collagen, a structural protein found in bones, was recovered and identified from a fossilized hadrosaur (Brachylophosaurus canadensis) bone dated to approximately 80,000,000 years ago (Schweitzer et al 2009). This study and others that demonstrate the preservation of biomolecules in ancient and/or experimental samples suggest that the potential for Stevens et al (2010). Four different proteins (bovine serum albumin, bovine casein, bovine collagen and horse myoglobin), were cooked with ceramic at different ratios.…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations
“…In one of the most surprising recent examples, collagen, a structural protein found in bones, was recovered and identified from a fossilized hadrosaur (Brachylophosaurus canadensis) bone dated to approximately 80,000,000 years ago (Schweitzer et al 2009). This study and others that demonstrate the preservation of biomolecules in ancient and/or experimental samples suggest that the potential for Stevens et al (2010). Four different proteins (bovine serum albumin, bovine casein, bovine collagen and horse myoglobin), were cooked with ceramic at different ratios.…”
Section: Introductionmentioning
confidence: 73%
“…Specifically, it has been demonstrated that proteins bind to mineral, e.g., ceramic, matrices via the interplay of inter and intra-molecular non-covalent forces including ion exchange, water bridges, Van der Waal bonding, and hydrophobic interactions ( Figure 1). Subsequently, these residues are difficult to remove and detect without the use of corrosive acids, strong detergents, and/or highly sensitive analytical equipment (Craig and Collins 2002;Stevens et al 2010). In addition to binding proteins, such matrices may also facilitate preservation by trapping organics within small pore spaces that restrict the access of microorganisms (Brady and Weil 2002:514) and/or within complex organic conglomerates (Kleber et al 2007).…”
Section: Protein Residuesmentioning
confidence: 99%
See 2 more Smart Citations
“…Much of this work has been done experimentally, and the audience is referred to Barker et al (2012Barker et al ( , 2015 and Stevens et al (2010) for details. For the purposes of this paper, suffice it to say that we used experimental cooking pottery to develop our approaches.…”
Section: Protein Residues From Archaeological Cooking Potterymentioning
confidence: 99%